SOX11-negative Mantle Cell Lymphoma: Clinicopathologic and Prognostic Features of 75 Patients. (May 2019) - Xu, Jie; Wang, Lifu; Li, Jingyi; Saksena, Annapurna; Wang, Sa A.; Shen, Jing; Hu, Zhihong; Lin, Pei; Tang, Guilin; Yin, C. Cameron; Wang, Michael; Medeiros, L. Jeffrey; et al.
Abstract : Studies have suggested that SOX11 expression has prognostic implications in patients with mantle cell lymphoma (MCL), but the data are controversial. In this study, we describe the clinicopathologic and prognostic features of 75 patients with SOX11-negative MCL. Compared with patients with SOX11-positive MCL, SOX11-negative MCL patients more frequently had leukemic non-nodal disease (21% vs. 4%, P =0.0001). SOX11-negative MCLs more often showed classic morphology (83% vs. 65%, P =0.005), were more often positive for CD23 (39% vs. 22%, P =0.02) and CD200 (60% vs. 9%, P =0.0001), and had a lower proliferation index (Ki67 23% vs. 33%, P =0.04). Overall survival (OS) was not significantly different between patients with SOX11-negative versus SOX11-positive MCL ( P =0.63). High Ki67 index and blastoid/pleomorphic morphology were associated with shorter OS in both SOX11-negative ( P <0.05) and SOX11-positive MCL groups ( P <0.05). A high Mantle Cell Lymphoma International Prognostic Index (MIPI) predicted poorer prognosis in patients with SOX11-negative MCL ( P <0.0001), but not SOX11-positive MCL ( P =0.09). Nodal involvement and stage III/IV disease were associated with poorer outcome in patients with SOX11-positive MCL ( P =0.03 and 0.04, respectively), but not SOX11-negative MCL ( P =0.88 and 0.74, respectively). In summary, SOX11-negative MCL is characterized by more frequent leukemic non-nodal disease, classic morphology, more frequent expression of CD23 and CD200, and a lower Ki67 index. Prognostic factors in patients with SOX11-negative MCL include morphology, Ki67 index, and MIPI score.